Evaluation of the Efficacy of Corticotomy and Piezocision on Canine Retraction: A Systematic Review - Erica Lipani; Elisa Pisani; Mariagrazia Verrone; Federica Bitonto; Alessio Verdecchia; Enrico Spinas (Dentistry Journal)
Background: In order to reduce the prolonged duration of orthodontic treatment, several surgical techniques have been proposed over the years. Corticotomy and piezocision are the two most widely used techniques, and, given the lack of consensus in the literature, along with the renewed interest in these approaches in recent years, the primary objective of this study is to evaluate their effectiveness in accelerating canine retraction in patients requiring extraction of the upper first premolar and, as a secondary objective, to assess if there is a worsening of periodontal health and how the surgical approach is perceived by the patient. Methods: An electronic search was performed on PubMed, Scopus, Web of Science, Embase, and the Cochrane Central Register of Controlled Trials (CENTRAL) up to 30 November 2024. The PRISMA statement was adopted for the realization of the review, and the Cochrane Collaboration’s risk of bias assessment tool (RoB 2) was used to assess the studies’ quality. Results: After full text assessment, fifteen randomized clinical trials (14 split mouth design, 1 single-blind, single-center design) covering 326 patients (mean age 20, 19 years) were included. The data collected reveal that corticotomy accelerates canine retraction by 1.5 to 4 times, while piezocision achieves retraction 1.5 to 2 times faster, making corticotomy the most effective technique. No statistically significant adverse effects on periodontal ligament, molar anchorage loss, or root resorption were observed following the two surgical techniques. In addition, patients reported experiencing mild to moderate pain. Conclusions: Corticotomy and piezocision are effective techniques for accelerating upper canine retraction in extraction cases, significantly reducing the overall duration of orthodontic treatment.